Influence of air exposure on structural isomers of silver nanoparticles - Richard Palmer (Communications Chemistry, 2023)
Up to date, the influence of ambient air exposure on the energetics and stability of silver clusters has rarely been investigated and compared to clusters in vacuum. Silver clusters up to 3000 atoms in size, on an amorphous carbon film, have been exposed to ambient air and investigated by atomic-resolution imaging in the aberration-corrected Scanning Transmission Electron Microscope. Ordered structures comprise more than half the population, the rest are amorphous. Here, we show that the most common ordered isomer structures is the icosahedron. These results contrast with the published behaviour of silver clusters protected from atmospheric exposure, where the predominant ordered isomer is face-centred cubic. We propose that the formation of surface oxide or sulphide species resulting from air exposure can account for this deviation in stable isomer. This interpretation is consistent with density functional theory calculations based on silver nanoclusters, in the size range 147-201 atoms, on which methanethiol molecules are adsorbed. An understanding of the effects of ambient exposure on the atomic structure and therefore functional properties of nanoparticles is highly relevant to their real-world performance and applications.